Hawking Radiation from non-evaporating primordial black holes cannot enable the formation of direct collapse black holes - Jonathan Regan; Marios Kalomenopoulos; Kelly Kosmo O'Neil (The Open Journal of Astrophysics, 2025)
The formation of supermassive black holes (SMBHs) in the early Universe is a subject of significant debate. In this study, we examine whether non-evaporating primordial black holes (PBHs) can offer a solution. We establish initial constraints on the range of PBH masses that correspond to Hawking radiation (HR) effective temperatures in the range needed to avoid the fragmentation of primordial gas into smaller, stellar-mass black holes. We also investigate the specific intensity of the HR from non-evaporating PBHs and compare it with the critical radiation needed for direct collapse black holes (DCBHs). We show that HR from non-evaporating PBHs cannot serve as the heating mechanism to facilitate the formation of the seeds for the SMBHs we observe in the high-redshift Universe unless, perhaps, the PBHs within the relevant mass range comprise a significant fraction of dark matter and are significantly clustered towards the center of the primordial halo.